3D structural and atomic-scale analysis of lath martensite: Effect of the transformation sequence. (15th August 2015) - Morsdorf, L.; Tasan, C.C.; Ponge, D.; Raabe, D.
Abstract: To improve the fundamental understanding of the multi-scale characteristics of martensitic microstructures and their micro-mechanical properties, a multi-probe methodology is developed and applied to low-carbon lath martensitic model alloys. The approach is based on the joint employment of electron channeling contrast imaging (ECCI), electron backscatter diffraction (EBSD), transmission electron microscopy (TEM), atom probe tomography (APT) and nanoindentation, in conjunction with high precision and large field-of-view 3D serial sectioning. This methodology enabled us to resolve (i) size variations of martensite sub-units, (ii) associated dislocation sub-structures, (iii) chemical heterogeneities, and (iv) the resulting local mechanical properties. The identified interrelated microstructure heterogeneity is discussed and related to the martensitic transformation sequence, which is proposed to intrinsically lead to formation of a nano-composite structure in low-carbon martensitic steels.